Odpowiedź:
a)
8 + 6*x -5-2*x=4*x+12-9*x
4*x + 3 = -5*x + 12 |+5*x
9x + 3 = 12 |-3
9x = 9 |:9
x = 1
spr
L = 8 + 6*x - 5 - 2*x = 8 + 6*1 - 5 - 2*1 = 8 + 6 - 5 - 2 = 7
P = 4*x + 12 - 9*x = 4*1 + 12 - 9*1 = 16 - 9 = 7
L=P
b)
-4 - 5*x + x + 6 = 7 - 2*x + 9 - 4*x
-4*x+ 2 = -6*x +16 |+6*x
2x + 2 = 16 |-2
2x = 14 |:2
x = 7
spr
L = -4 - 5*x + x + 6 = -4 - 5*7 + 7 + 6 = -4 - 35 + 7 + 6 = -39 + 13 = -26
P = 7 - 2*x + 9 - 4*x = 7 - 2*7 + 9 - 4*7 = 7 - 14 + 9 - 28 = 16 - 42 = -26
L=P
Szczegółowe wyjaśnienie: